Menu-Match: Restaurant-Specific Food Logging from Images - Beijbom, Oscar; Joshi, Neel; Morris, Dan; Saponas, Scott; Khullar, Siddharth (Applications of Computer Vision (WACV), 2015 IEEE Winter Conference on, 2015)
Logging food and calorie intake has been shown to facilitate weight management. Unfortunately, current food logging methods are time-consuming and cumbersome, which limits their effectiveness. To address this limitation, we present an automated computer vision system for logging food and calorie intake using images. We focus on the “restaurant” scenario, which is often a challenging aspect of diet management. We introduce a key insight that addresses this problem specifically: restaurant plates are often both nutritionally and visually consistent across many servings. This insight provides a path to robust calorie estimation from a single RGB photograph: using a database of known food items together with restaurant-specific classifiers, calorie estimation can be achieved through identi- fication followed by calorie lookup. As demonstrated on a challenging Menu-Match dataset and an existing thirdparty dataset, our approach outperforms previous computer vision methods and a commercial calorie estimation app. Our Menu-Match dataset of realistic restaurant meals is made publicly available.